Japan's Restrictive System of Trade and Payments : Operation, Effectiveness, and Liberalization, 1950-1964 - Takagi, Shinji (IMF Working Papers; Working Paper ;, 1997)
The paper summarizes how Japan's foreign exchange and trade control system operated in the early 1950s, how and how effectively it was used as a tool of external adjustment, and how it was liberalized from the late 1950s into the early 1960s. Although the Japanese government was extensively involved in allocating scarce foreign exchange in the early 1950s, the control system became increasingly flexible over this period. A preliminary analysis based on the behavior of wholesale prices seems to indicate that, along with its liberalization, the restrictive system became less effective as a tool of external adjustment, while the impact of deflationary macroeconomic measures became more dominant.